EVALUATION OF ENVIRONMENTAL POLLUTION AT MUNZUR RIVER OF TUNCELI APPLYING OXIDATIVE STRESS BIOMARKERS IN CAPOETA TRUTTA (HECKEL, 1843) - N. C. Yildirim; F. Benzer; D. Danabas (Journal of Animal and Plant Sciences, 2011)
Aim of this study was to determine the extent of pollution in the Munzur River in Turkey was determined. The antioxidant (reduced glutathione (GSH), glutathione peroxidase (GSH-Px) catalase (CAT)) and the oxidant (MDA) status of hepatopancreas, gills, muscle, heart and kidney tissues of C. trutta were chosen as bioindicators. The fish samples were caught from contaminated (Station I) and uncontaminated (Station II) stations in Munzur River during April 2010. GSH levels were lower in gill, muscle and heart of the C. trutta collected at the contaminated station (p<0.05).  The MDA levels were significantly higher in gill, muscle, kidney and heart of the C. trutta from the contaminated station (p<0.05). The CAT activity was significantly increased in the gill tissue at the contaminated station (p<0.05). GSH-Px activity was significantly decreased (p<0.05) in gill, muscle, kidney and heart tissues samples from C. trutta collected at the contaminated station compared to those collected from the uncontaminated station. Overall, the results demonstrate that alteration in the antioxidant enzymes, glutathione system and induction of lipid peroxidation reflects the presence of pollution, which may cause oxidative stress in the C. trutta from Munzur River. The results provide evidence those enzymatic and non-enzymatic biomarkers of oxidative stress.
Keywords: Capoeta trutta; Munzur River; Pollution; Oxidant and antioxidant status